The Prophet king - Khan, Saniyasnain (Goodword : India, 2011)
The Prophet King narrates the story of Prophet Dawud (David), highlighting his wisdom, justice, and leadership. The book emphasizes his role as a prophet and a king, illustrating how he upheld fairness and righteousness in his reign. Through simple language and vibrant illustrations, the story captures the essence of Prophet Dawud's character and his contributions to his people.